Direct imaging of native passive film on stainless steel by aberration corrected STEM - Hamada, Etsuo; Yamada, Katsumi; Nagoshi, Masayasu; Makiishi, Noriko; Sato, Kaoru; Ishii, Tomohiro; Fukuda, Kunio; Ishikawa, Shin; Ujiro, Takumi (Corrosion science, 2010)
A cross-section of a native passive film on a commercial type 304 stainless steel was directly imaged and characterized using an aberration corrected STEM-EDS in combination with FIB sectioning. The technique demonstrated an enrichment of Cr in the lower part of the passive film, and a depletion of Cr and an enrichment of Ni in the matrix side closest to the passive film/matrix interface in accordance with previous studies, further proving the advantage of this technique with respect to spatial resolution. That is, the STEM-EDS showed a compositional profile with higher spatial resolution compared to AES which has been mainly used for this type of investigation. The technique will be applicable to the investigation of nm to sub-nm compositional fluctuation of passive films, steel surfaces adjacent to inclusions and grain boundaries postulated as an initiating site of pitting corrosion or stress corrosion cracking (SCC).